Familialization of women: Gender ideology in Turkey's public service advertisements - NAS, ALPARSLAN (My University, 2016)
In Turkey, Justice and Development Party (AKP) holds a single-party government since 2002 with a conservative, pro-Islamist and anti-feminist political ideology. AKP’s authoritarian tone towards women increased particularly after 2011 when the party gained its third consecutive election victory. In this regard, the abolishment of “The Ministry of Women and Family” and instead the foundation of “The Ministry of Family and Social Policies” (MFSP) in 2011 was criticized by feminist activism, with the claim that the attempt erases the name of women from the ministry which might lead to devastating effects on the solution of women’s issues. Focussing on advertisements as ideological apparatuses, this article undertakes a critical analysis of Public Service Advertisements (PSAs) with a total number of 30 spots broadcast on TV by MFSP since 2012. Problematizing the representation of women in PSAs, this article aims to analyse the practices of women’s familialization by means of the concealment of women’s issues and legitimization of patriarchy.

Türkiye’de 2002 yılından günümüze dek tek başına iktidarını sürdüren AKP dönemi, toplumsal cinsiyet bağlamında muhafazakar, İslamcı veya anti-feminist olarak nitelenedirilebilecek birtakım politikaların uygulayıcısı olmuştur. Özellikle AKP’nin üçüncü seçim zaferini kazandığı 2011 yılından itibaren kadına yönelik söylemlerin otoriter tonu giderek yükselmiştir. Bu bağlamda, 2011 yılında “Kadın ve Aileden Sorumlu Devlet Bakanlığı”nın kapatılarak yerine “Aile ve Sosyal Politikalar Bakanlığı” (ASPB) kurulması feminist aktivizmin eleştiri odağı olmuş, “kadın” ifadesini bakanlıktan silen bu girişimin kadınların sorunlarının çözümünü olumsuz etkileyebileceği vurgulanmıştır. Politik alanda kadına yönelik söylemlerin bir yansıması olarak reklam olgusunu ele alan bu makale, ASPB tarafından 2012 yılından itibaren günümüze dek yayınlanan 30 adet kamu spotunu eleştirel açıdan incelemektedir. Kamu spotlarında kadının temsilini sorunsallaştıracak olan bu makale, resmi söylemin kadının sorunlarını görünmez hale getirme ve patriyarkayı meşrulaştırma suretiyle kadını ailevileştirilme pratiklerini analiz etmeyi hedeflemektedir.
Keywords: AKP; Family; Gender; Public Service Advertisements; Women in Turkey; Aile; Kamu Spotu; Toplumsal Cinsiyet; Türkiye’de Kadın